STATUS EFFECT ON CHILDREN OUTSIDE MARRIED STATUS AFTER CONSTITUTIONAL RELIGIOUS COURT DECISION - Sulaiman Sulaiman (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
The purpose of this study as follows 1) To identify and explain Child outside influence married status of the right to inherit after the Constitutional Court decision No. 46/PUU-VIII/2010 in the Religious Court Kendari, 2) To identify and explain the barriers outside the married status of children of the right to inherit after the decision of the Constitutional Court Number 46/PUU-VIII/2010 in the Religious Court Kendari, 3) To identify and explain solutions to overcome barriers outside the married status of children of the right to inherit after the decision of the Constitutional Court Number 46/PUU-VIII/2010 in the Religious Court Kendari. The method used by researchers is sociological approach juridical law and specification in this study were included descriptive analysis. The sources and types of data in this study are primary data obtained from field studies with interview Religious Court Judge in Kendari. And secondary data obtained from the study of literature. Based on the results of the research are In terms of inheritance after the court ruling, the position of a child outside of married as intended by the constitutional court decision outside the married is not the same child with the natural child, has been gaining street or space to get recognition for the sake of protection of the rights of the child outside the married. In this case the Constitutional Court to decide Article 46/PUU-VIII/2010 on children outside of married, deserved to be recognized by the biological father and is also entitled to inheritance equal to the other children. Constraints in this Constitutional Court decision is a matter of perspective among law enforcement and government officials to give up the rights to illegitimate children are no different treatment or other discriminatory treatment.